Raltegravir, Indinavir, Tipranavir, Dolutegravir, and Etravirine against main protease and RNA-dependent RNA polymerase of SARS-CoV-2: A molecular docking and drug repurposing approach - Purushothaman Indu; Marimuthu Ragavan Rameshkumar; Narasingam Arunagirinathan; Naif Abdullah Al-Dhabi; Mariadhas Valan Arasu; Savarimuthu Ignacimuthu (Elsevier, 2020)
Background: Outbreak of COVID-19 has been recognized as a global health concern since it causes high rates of morbidity and mortality. No specific antiviral drugs are available for the treatment of COVID-19 till date. Drug repurposing strategy helps to find out the drugs for COVID-19 treatment from existing FDA approved antiviral drugs. In this study, FDA approved small molecule antiviral drugs were repurposed against the major viral proteins of SARS-CoV-2. Methods: The 3D structures of FDA approved small molecule antiviral drugs were retrieved from PubChem. Virtual screening was performed to find out the lead antiviral drug molecules against main protease (Mpro) and RNA-dependent RNA polymerase (RdRp) using COVID-19 Docking Server. Furthermore, lead molecules were individually docked against protein targets using AutoDock 4.0.1 software and their drug-likeness and ADMET properties were evaluated. Results: Out of 65 FDA approved small molecule antiviral drugs screened, Raltegravir showed highest interaction energy value of -9 kcal/mol against Mpro of SARS-CoV-2 and Indinavir, Tipranavir, and Pibrentasvir exhibited a binding energy value of ≥−8 kcal/mol. Similarly Indinavir showed the highest binding energy of -11.5 kcal/mol against the target protein RdRp and Dolutegravir, Elbasvir, Tipranavir, Taltegravir, Grazoprevir, Daclatasvir, Glecaprevir, Ledipasvir, Pibrentasvir and Velpatasvir showed a binding energy value in range from -8 to -11.2 kcal/mol. The antiviral drugs Raltegravir, Indinavir, Tipranavir, Dolutegravir, and Etravirine also exhibited good bioavailability and drug-likeness properties. Conclusion: This study suggests that the screened small molecule antiviral drugs Raltegravir, Indinavir, Tipranavir, Dolutegravir, and Etravirine could serve as potential drugs for the treatment of COVID-19 with further validation studies.